Spandrel

JP7637688B2Active Publication Date: 2025-02-28AGC GLASS EUROPE SA +3
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022543085
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-16
Filing Date
2021-01-11
Publication Date
2025-02-28
Estimated Expiration
2041-01-11

Smart Images

  • Figure 0007637688000010
    Figure 0007637688000010
  • Figure 0007637688000011
    Figure 0007637688000011
  • Figure 0007637688000012
    Figure 0007637688000012
Patent Text Reader

Abstract

The present invention relates to a spandrel comprising a first substrate, an intermediate film made of a polymer material, and a second opaque substrate, characterized in that the first substrate is covered with up to two layers, including at least one upper dielectric layer, deposited on a surface arranged opposite the intermediate film made of a polymer material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a spandrel panel incorporating at least one glazing panel and intended to be placed in an area of ​​a facade that is not intended to transmit light. Its role is therefore to conceal certain parts of this facade between the parts occupied by the windows. More specifically, the present invention discloses a spandrel panel that ensures good aesthetics by blending with the adjacent transparent glazing. The spandrel panel of the present invention is an assembly of at least two substrates, one of which is transparent and the other opaque. The external substrate (i.e. the external in relation to the building) has good light transmission, which means that the spandrel panel of the present invention serves for the insertion of solar cells in its interior. Such a spandrel panel is therefore intended to be used in a facade to form a so-called building integrated photovoltaic (BIPV). [Background technology]

[0002] In many modern constructions, the glazing walls contain transparent and opaque areas. The window itself may be relatively transparent or relatively reflective depending on the properties of the coating carried by the glass. These coatings, which are almost essential, give the glazing advantageous thermal properties, such as solar control and low emissivity properties. By appropriate selection of the material and / or its thickness, it is possible to achieve pleasant colors in reflection and / or transmission, such as blue, green, bronze or neutral tones, which are generally preferred. Other properties that the glazing may need to have are, for example, self-cleaning properties, anti-fogging properties, or any other properties required by the customer or required by the situation.

[0003] According to another aspect, and for various reasons, glazings intended for such buildings must be heat treated, in particular for safety reasons, which means that they must be subjected to temperatures of more than 500° C., or even more than 600° C., for several minutes and according to methods well known in the art. This means that any coating carried by the glass must be capable of undergoing this treatment without degradation, i.e. its optical and energetic properties must not be altered or significantly altered by the heat treatment.

[0004] The spandrel panels are either inherently opaque or are opaqued by various covering or cladding systems. However, even if the spandrel panels are opaque to visible light, they must match the tint in reflection of the adjacent windows. The entire glazing façade must appear optically uniform from the outside at all viewing angles, both in relation to the light reflection and its tint shading.

[0005] Several methods are known in the art for providing suitable spandrel panels. For many years, it has been known to opacify glass substrates with colored enamels. In particular, US Pat. No. 3,951,525 suggests depositing an opaque enamel on a reflective metal oxide, the metal oxide being the same as that used for the façade windows. The problem with this solution is that it is not optimally matched and, moreover, is not stable over time.

[0006] WO 2004 / 092522 A1 suggests a spandrel panel in the form of a double glazing, the inner glass (i.e. the glass facing the building) of which has a very low transmittance (less than 15%) and the outer glass of which is covered with a solar control laminate to prevent people from looking in. Such a construction is expensive and does not fully meet the aesthetic requirements of modern glass facades.

[0007] It is also suggested to make the metal layers opaque, for example in EP 0 441 011 or EP 3 172 175. These metal layers are generally included in relatively complex stacks. The two aforementioned patent documents suggest in particular a specific relationship between the refractive index and the absorption coefficient. The stack also requires the presence of a dielectric to adjust the optical properties.

[0008] EP 2517877 discloses a laminated glazing in which the external substrate is opacified by means of an absorbing laminate in contact with the PVB used as adhesive between the two substrates. The basic feature of this invention is that the glass covered by the opacifying laminate is an extra clear glass that contains almost no iron and therefore has very little absorption itself. This feature has the advantage, according to the inventor, of making it possible to avoid harsh heat treatments. However, the patent is silent about the manner in which the tint can be matched to the window, and in addition to this, this type of solution inevitably brings about problems with storage costs.

[0009] In conclusion, enamel and paint are limited and expensive solutions (additional heating step) and do not always meet aesthetic requirements. The visual appearance of panels simply colored with enamel or paint does not meet current requirements. None of the prior art solutions allow the glass panels to be heat treated. These solutions are sometimes unacceptable for inventory reasons. Requirements in relation to color matching are often not met.

[0010] In addition to this, new challenges arise as a result of current environmental problems, apart from those related to aesthetics, costs and durability. Buildings are increasingly being equipped with solar cells to collect energy from the sun and convert it into electricity. Initially, solar cells were mainly installed on the roof, but now there is an increasing demand for solutions that allow them to be installed on the facades. A first solution involves installing solar cells in windows, which requires finding ways to hide them from view or to make them aesthetically acceptable. Another possibility is to hide them in spandrel panels, which obviously requires taking measures to allow the light to reach the solar cells without negatively affecting the aesthetics as a whole and without significant losses in efficiency.

[0011] Today's architects want an all-ready solution that meets the requirements in terms of aesthetics (color, reflection, harmony) and thermal performance. The solutions of the prior art do not offer an all-ready solution that has an acceptable manufacturing cost, meets the aesthetic requirements, and in addition provides a spandrel panel that can incorporate solar cells. This is exactly what the present invention proposes, and in addition has good chemical resistance and mechanical strength. Summary of the Invention

[0012] The inventors have discovered that spandrel panels may be advantageously formed by laminating a first substrate and a second substrate utilizing an intermediate sheet of polymeric material provided for adhesion purposes. Throughout this description, the first substrate is the substrate furthest from the building and is therefore the outermost substrate.

[0013] The first substrate is covered by an upper dielectric layer, characterized on the one hand by a sufficiently large refractive index and on the other hand by a sufficiently small absorption coefficient. These characteristics allow the realization of an external reflection of a pleasant color and a good light transmission. The color in the external reflection can be adjusted through a suitable selection of the layer thickness and / or its properties. A suitable selection of the material properties allows the requirements in terms of resistance to heat treatment and durability to be met.

[0014] The first substrate is bonded to the second substrate utilizing an intermediate polymeric material to form a laminate, and a top dielectric layer is deposited on the first substrate on a side oriented toward the intermediate polymeric material (i.e., at position P2).

[0015] According to a first embodiment, the upper dielectric layer is in direct contact with the first substrate.

[0016] According to a second embodiment, the first substrate of the invention is covered by an underlayer arranged between the first substrate and the upper dielectric layer, the underlayer being a barrier layer whose role is to protect the layer of the invention when the properties of the layer do not provide sufficient resistance to heat treatments.

[0017] In each embodiment, the second substrate is opaque.

[0018] Preferably, the upper dielectric layer and the lower layer are the only layers deposited on the first substrate.

[0019] In one particular embodiment of the invention, a solar cell is disposed between two substrates of a laminate according to any of the above-described embodiments. [Brief description of the drawings]

[0020] To facilitate understanding, the figures presented below are not drawn to scale. [Figure 1] 1 is a cross-section of a first substrate intended for a first embodiment. [Diagram 2]4 is a cross-section of a first substrate intended for a second embodiment. [Diagram 3] 1 is a cross-section of a laminate according to a first embodiment of the present invention. [Figure 4] 4 is a cross-section of a laminate according to a second embodiment of the present invention. [Diagram 5] 1 is a cross-section of a particular embodiment of the invention having a solar cell according to a first embodiment. [Figure 6] 4 is a cross-section of a particular embodiment of the invention having a solar cell according to a second embodiment. [Figure 7] 1 is a cross section of a laminate according to an alternative embodiment of the invention, in which the second substrate is a pane of ordinary glass opacified with a black film of PET. [Figure 8] 8 is a cross-section of one particular embodiment of the present invention having a solar cell according to the alternative embodiment shown in FIG. 7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The present invention relates to a laminated assembly (laminate) comprising a first substrate and a second substrate held together by an intermediate sheet of polymeric material extending over at least an area of ​​each of the two substrates.

[0022] The first substrate is the external substrate, i.e. the substrate furthest from the building. Preferably, it is a glass substrate. Glass means a transparent mineral glass mainly made from silica, such glass includes in particular regular soda-lime float glass, the thickness of which is between 0.5 and 20 mm, preferably between 1.5 and 10 mm, and even more preferably between 2 and 6 mm. Advantageously, this first substrate may be made of clearer or even extra clear soda-lime glass, which means that it is characterized by a low total iron content, expressed in Fe2O3, in particular by a total iron content, expressed in Fe2O3, of at most 0.015% by weight for extra clear glass and 0.1% by weight for clear glass. The consequence of such a low iron content is that the energy transmission of the glass is much better, in particular more than 90% for extra clear glass, compared to 82% for regular float glass with a thickness of 5 mm. The advantage of improved energy transmission is that solar cells can achieve relatively good efficiency when placed behind such glass.

[0023] The optical reflectance and transmittance are given according to standard EN 410 (2011). They are measured using a light source according to the standard illuminant D65 defined by the CIE (International Commission on Illumination) in a solid angle of 2°.

[0024] The external reflectance, i.e. the reflectance on the uncoated side of the glass, for a monolithic pane of glass, i.e. an unlaminated pane of glass, is R g In the case of laminate, it is written as R ext It is written as follows.

[0025] The color parameters are given by their coordinates in the CIELAB color space. * Rg and b * Rgis the color parameter a measured in external reflection from the monolithic substrate (i.e., measured on the uncoated side of the glass); * and b * It means Y Rg and L Rg * are the reflectance expressed as a percentage and the luminous intensity (brightness) expressed as a percentage, respectively, measured on the uncoated side of the glass. The corresponding color parameters measured on the outer side of the laminate, i.e., on the uncoated side of the first substrate, are R ext , a * ext , and b * ext It is written as follows.

[0026] The reflectance of the coated side of a monolithic pane of glass is R c The corresponding color parameters are given by their coordinates in the CIELAB color space. * Rc and b * Rc is the color parameter a measured in reflection of the coating side on the monolithic substrate * and b * It means Y Rc and L Rc * means the reflectance expressed as a percentage and the luminous intensity (brightness) expressed as a percentage, measured on the coated side of the glass. The light transmittance in the visible spectrum is according to standard EN410 (2011). It is denoted as Tv and the corresponding color parameter is a * Tv and b * Tv is given by:

[0027] The energy transmission (TE) corresponds to the transmission of a larger part of the solar spectrum than the transmission of visible light. This information is particularly important when it is the transmitted light energy that tends to interact with the solar cell of interest. In this description, the energy transmission is measured according to standard EN410 (2011) for light with wavelengths between 300 and 2500 nm. For these, simulations of the energy transmission were also performed for light with wavelengths between 390 and 2500 nm.

[0028] The composition of the mixed oxides or nitrides is indicated by a ratio that represents the weight percentage of the two components of the dielectric, the first number relating to the first element of interest. Thus, TZO65 / 35 means a mixed titanium-zirconium oxide composed of 65% by weight titanium oxide and 35% by weight zirconium oxide. Similarly, SiZrN60 / 40 means a mixed nitride composed of 60% by weight silicon nitride and 40% by weight zirconium nitride. The mixed oxide ZSO5 52 / 48 corresponds to a mixed zinc-tin oxide composed of 52% by weight zinc oxide and 48% by weight tin oxide, i.e. ZSO5 is zinc stannate (Zn2SnO4).

[0029] The upper dielectric layer is characterized by a high refractive index and a low absorption coefficient. Preferably, the refractive index of the upper dielectric layer is at least 2.0, preferably at least 2.1. Advantageously, the absorption coefficient of the dielectric layer is at most 0.1, preferably at most 0.05. The refractive index has an impact on the aesthetic appearance (color in reflection), while the low absorption coefficient allows a relatively large energy transmission.

[0030] Advantageously, the upper dielectric layer is selected from mixed oxides, nitrides or oxynitrides, i.e. mixed oxides, nitrides or oxynitrides comprising at least two different oxides, at least two different nitrides, at least two different oxynitrides (or at least one oxide and one nitride of two different atoms). In the case of nitrides in particular partial oxidation can result in the formation of a mixed oxynitride.

[0031] Preferably, the oxide or nitride of which the dielectric layer of the present invention is composed is selected from oxides, nitrides, or oxynitrides of elements selected from silicon, titanium, zinc, tin, zirconium, aluminum, and niobium, such as, for example, mixed titanium-zirconium oxide (TZO) or mixed silicon-zirconium nitride (SiZrN).

[0032] In all cases, each oxide, nitride or oxynitride forming part of the composition of the upper layer is present in a proportion that is greater than or equal to 20% by weight, preferably greater than or equal to 25% by weight, and even more preferably greater than or equal to 30% by weight. More particularly, when the dielectric layer is a zirconium-titanium oxide, the weight percentage of titanium oxide is between 62 and 68% by weight. This choice in the context of mixed oxides, nitrides or oxynitrides advantageously makes it possible to combine the optical properties of one of the oxides, nitrides or oxynitrides of the mixture with the durability properties of another oxide, nitride or oxynitride of the mixture.

[0033] The optical thickness of the upper dielectric layer and its composition are selected according to the desired color in reflection. This thickness is advantageously at least 40 nm, preferably at least 50 nm.

[0034] Advantageously, this optical thickness is at most 110 nm, preferably at most 80 nm and even more preferably at most 70 nm.

[0035] In the laminate, the coating is placed on the inner part of the outer substrate, i.e. on the side of the sheet of polymeric material. Those skilled in the art usually refer to this side as position 2, and the sides of the glass sheets of the glazing that are placed inside the building are numbered from the outside to the inside.

[0036] According to a second embodiment of the invention, an underlayer is deposited on the first substrate between said substrate and the upper dielectric layer. The role of the underlayer is to protect the upper dielectric layer, and it may be any oxide, nitride or oxynitride capable of playing this role. By way of example, mention may be made of oxides of one or more elements selected from silicon, tin, zinc, titanium, aluminum, niobium and zirconium. Advantageously, the characteristics and thickness of this barrier layer are chosen so as not to modify the optical properties provided by the upper dielectric layer to the first substrate. More particularly, a layer of mixed zinc-tin oxide (ZSO), more particularly zinc stannate, is well suited to play the role of this barrier layer. Advantageously, the geometric thickness of the underlayer is at least equal to 5 nm, preferably at least equal to 10 nm, and is equal to or less than 25 nm, preferably equal to or less than 20 nm.

[0037] In each embodiment, the lower and upper dielectric layers can be applied using a cathode sputtering technique (sputtering is a type of PVD) under conventional conditions well known in the art for use with this type of technique. By using a metal target, nitrides are deposited in a reactive atmosphere of nitrogen and argon, and oxides are deposited in a reactive atmosphere of oxygen and argon. In a variant, the dielectric layers are applied using a well-known technique called PECVD (Plasma-Enhanced Chemical Vapor Deposition).

[0038] Advantageously, the coated first substrate has a glass side optical reflectance (R ) characterized by the values ​​shown in Table 1. g ) and the tint of the glass side in reflection. The values ​​in Table 1 are for a monolithic pane of glass after tempering. TIFF0007637688000001.tif47170

[0039] This coated and tempered first substrate is characterized by a sufficiently high energy transmission: in all cases the energy transmission for light of wavelengths between 300 and 2500 nm is greater than 0.68, preferably greater than 0.70, more preferably greater than 0.72, even more preferably greater than 0.74. The heat treatment advantageously applied to the first substrate comprises heating the substrate, in a manner well known to the skilled person, to a temperature of greater than 500° C., or even greater than 600° C., for a time period of greater than 4 minutes.

[0040] According to two embodiments of the invention, the first substrate is laminated with the second substrate by means of at least one intermediate film of a polymeric material inserted between the two substrates. One of the objectives of the invention is that the spandrel panels thus formed meet certain aesthetic criteria (see Table 2 below). The second substrate of the laminated assembly of the invention is opaque. It may be organic or inorganic in nature, or even a composite, organic or inorganic in nature. Advantageously, the second substrate of the laminate of the invention is an opaque polymer, such as, for example, polyvinyl fluoride, and in particular, the polyvinyl fluoride sold by DuPont under the name "Tedlar". In another embodiment, the second substrate is a glass substrate, opacified, for example, using a black paint, to form an assembly sold by the company AGC Glass Europe under the name "Lacobel black classic". In an alternative embodiment, the second substrate may also consist of a plurality of (organic or inorganic) elements deposited successively on an intermediate film of a polymeric material. Thus, for illustrative purposes, according to one alternative embodiment, an opaque polymer film (e.g., a black film of polyethylene terephthalate (PET)), a layer of ethylene vinyl acetate (EVA) and finally a pane of pre-tempered float glass are deposited to obtain a laminate that can be represented as, for example, coated first substrate / intermediate film / black PET / EVA / regular glass (said laminate is also shown diagrammatically in Figures 7 and 8).

[0041] In each embodiment, the intermediate film of polymeric material is advantageously selected from polyvinyl butyral (PVB), ethylene vinyl acetate (EVA), polyvinyl chloride (PVC), polyurethane (PU), ionomers or any other polymer having the required properties, such as, for example, thermoplastic polyolefins from Dow. The intermediate film of polymeric material has a thickness of 0.3 to 2 mm. This intermediate film may be a superposition of several sheets of the same or different materials. The two substrates are assembled using methods known to those skilled in the art and described, for example, in WO 2003 / 084744 A1 or BE 876681 A. The first substrate is covered with a polymer sheet unwound from a roll, which is then cut to the dimensions of the first substrate before the second substrate is placed on top of it. The assembly thus formed is calendered and autoclaved after degassing. This assembly method is given for illustrative purposes, any other method of assembling a laminate can be used for the present invention.

[0042] The laminate obtained according to any embodiment of the present invention is characterized by the desired optical properties, such as those shown in Table 2. The target values ​​are therefore primarily related to the aesthetic appearance in external reflection (external reflectance and color parameters in external reflection). TIFF0007637688000002.tif47170

[0043] Advantageously, the first substrate has a high energy transmission, so that it is possible to add a solar cell between the first and second substrates of the laminate, and to fix them, an intermediate sheet of polymeric material can be utilized. In this case, the first substrate is covered by a first intermediate film of polymeric material, after which the solar cell is placed on this film, electrical connections are made to the cell, and the assembly thus formed is covered by a second film of polymeric material. Finally, the second substrate is placed on the second film of polymeric material, and the assembly thus formed is laminated using methods well known to those skilled in the art (see above). The second substrate can have an inorganic character (glass), an organic character (Tedlar, etc.), or a composite character (opaque film and glass).

[0044] For an alternative embodiment where the second substrate is made from clear glass, the laminated assembly can be represented as coated substrate 1 / polymer film / solar cell / polymer film / black PET / EVA / substrate 2.

[0045] In this particular embodiment, the invention thus results in a spandrel panel equipped with solar cells that has a particularly advantageous aesthetic appearance and is almost impossible to observe, such a spandrel panel thus forming a BIPV element when used on a facade and having the advantage of being aesthetic and the benefit of collecting solar energy.

[0046] Advantageously, the thickness of each intermediate polymer film is between 0.3 and 2 mm, since the solar cell has a thickness between 0.1 and 1.0 mm.

[0047] For aesthetic reasons, it is known to conceal the edges of the cells, or to conceal the electrical connections and any parts as well, in order to create a discontinuity in the appearance of the finished product. One of the great advantages of the present invention is that, due to the opaque second substrate, most of the cells remain impossible to observe from the outside, and therefore only some particularly highly reflective connections have to be concealed, for example using a coating of black polyvinyl fluoride or paint. The junction box, the role of which is to collect the electricity generated by the panel, can advantageously be placed behind or to the side of the spandrel panel.

[0048] Detailed Description of the Invention The present invention will now be described with the aid of figures and examples, it being understood that the examples are given for illustrative purposes only and are not intended to limit the invention in any way.

[0049] definition By spandrel panel is meant herein an opaque panel intended for use on a building facade in the area between windows. By opaque substrate is meant a substrate having a light transmission of at most 4%, preferably at most 1%, and even more preferably at most 0.5%.

[0050] What is meant by optical thickness is the product of its refractive index multiplied by the geometric thickness of a material. By default, and unless otherwise stated, this is a matter of geometric thickness.

[0051] The refractive index and extinction coefficient are concepts well known to those skilled in the art. In this description, and unless otherwise stated, the values ​​of the refractive index, extinction coefficient, and optical thickness are given for a wavelength of 589 nm and were estimated using CODE-Theiss, an optical simulation software package.

[0052] For illustrative purposes, Table 3 shows the refractive index and extinction coefficient values ​​for several dielectric materials. Unless otherwise noted, the values ​​provided are simulated values ​​as described above. A value of zero for the extinction coefficient means that the simulated value was less than 0.0001. In the case of mixed oxides or nitrides shown in the table, the added ratios indicate the corresponding weight percentages of the components. For example, TZO65 / 35 refers to a mixed oxide composed of 65% titanium oxide and 35% zirconium oxide by weight. These values ​​will also be used for materials referenced in the remainder of this specification. TIFF0007637688000003.tif116170

[0053] drawing 1 shows in cross section a first substrate (S1) of a laminate according to the invention, said substrate being intended for a first embodiment. The first substrate has two main faces (1) and (2). A top dielectric layer L is deposited on face (2) according to the invention by PVD or PECVD.

[0054] Figure 2 shows in cross section a first substrate (S1) of a laminate according to the invention, said substrate intended for the second embodiment. The first substrate has two main faces (1) and (2). A first underlayer B is deposited on face (2) and then a top dielectric layer L is deposited according to the invention on the underlayer B. Both layers are deposited by PVD or PECVD.

[0055] Figure 3 shows in cross section a laminate according to a first embodiment of the invention: a first substrate (shown in Figure 1) is laminated with a second substrate (S2) by means of an intermediate sheet (P1) of polymeric material deposited on the side of face (2) of the first substrate, this face being the face covered by the upper dielectric layer (L).

[0056] Figure 4 shows in cross section a laminate according to a second embodiment of the invention: a first substrate (shown in Figure 2) is laminated with a second substrate (S2) by means of an intermediate sheet (P1) of polymeric material deposited on the side of face (2) of the first substrate, this face being the face covered by the underlayer (B) and by the upper dielectric layer (L).

[0057] Figure 5 shows in cross-section a particular embodiment of the invention in which a second intermediate sheet of polymeric material (P2) is added to the laminate shown in Figure 3 and the solar cells (PV) are positioned between the two intermediate sheets (P1) and (P2).

[0058] Figure 6 shows in cross-section a particular embodiment of the invention in which a second intermediate sheet of polymeric material (P2) is added to the laminate shown in Figure 4 and the solar cells (PV) are positioned between the two intermediate sheets (P1) and (P2).

[0059] Figure 7 shows an alternative embodiment in cross section where the second substrate is a regular pane of glass opacified with a black polymeric film made from PET, which is securely adhered to the glass by a film made from EVA. The alternative embodiment shown in Figure 7 shows the second embodiment, where a bottom layer (B) is placed below an upper dielectric layer (L).

[0060] Figure 8 shows in cross-section a particular embodiment of the invention in which a second intermediate sheet of polymeric material (P2) is added to the laminate shown in Figure 7 and the solar cells (PV) are positioned between the two intermediate sheets (P1) and (P2). EXAMPLES

[0061] According to a first embodiment, the top dielectric layer of the invention is deposited on a first substrate. Table 4 shows the optical parameters obtained from simulations carried out by the Theiss CODE system for top dielectric layers made from various types of dielectric. In these examples, the dielectric has a geometric thickness of 27 nm and is deposited on a clear glass of a thickness of 3.85 mm, of the type sold by AGC under the name Clearlite. The simulated values ​​are given for a monolithic substrate. The energy transmittance was simulated based on calculations according to standard EN410 (2011) for the wavelength range of 390-2500 nm. TIFF0007637688000004.tif103170

[0062] Further according to the first embodiment, a glazing was simulated with TZO65 / 35 as dielectric layer deposited on a first substrate (3.85 mm float glass). Table 5 shows the optical parameters obtained for various thicknesses of TZO65 / 35. The thickness is the geometric thickness and is given in nm. The values ​​were obtained through simulations carried out using the Theiss CODE system. The simulated values ​​are given for a monolithic substrate. The energy transmittance was simulated based on calculations according to standard EN410 (2011) in the wavelength range of 390-2500 nm. TIFF0007637688000005.tif182170

[0063] Examples 1 to 4 of the realization of the present invention according to the first embodiment An extra clear glass panel with a thickness of 4 mm was introduced into the vacuum chamber of a magnetron cathode sputtering device. The vacuum chamber was equipped with a ceramic cathode made of titanium-zirconium oxide (65 / 35). By using methods well known to those skilled in the art, a layer of TZO 65 / 35 was deposited on the glass substrate in an oxygen and argon atmosphere. The conditions were adjusted to obtain four coated examples described in Table 6, in which the thickness of the deposited layer differed. TIFF0007637688000006.tif41170

[0064] The samples were heat treated (held at 670° C. for 4 min). In each case, all the optical parameters in reflection or in transmission (Y, L) were measured before and after the heat treatment. * , a * , b * ) remained in a stable condition.

[0065] Some samples were laminated with a Tedlar substrate with an EVA polymer film and in such a way as to incorporate a solar cell. The optical parameters of the laminated assemblies were measured with an Ultrascan spectrophotometer and are shown in Table 7. The color parameters are shown for reflection on the external side, i.e. from the uncoated side of the glass substrate of the laminate. TIFF0007637688000007.tif58170

[0066] The presence of the opaque second substrate and the resulting advantageous reflectance causes everything behind the first substrate to be optically lost, thus allowing the laminate to be used as a spandrel panel due to its particularly attractive aesthetic appearance.

[0067] Examples 8-9 of the realization of the present invention according to the second embodiment In a second embodiment of the invention, a barrier layer is deposited on the first substrate before the deposition of the dielectric layer of the invention. An extra clear glass panel with a thickness of 4 mm was introduced into the first vacuum chamber of the magnetron coating apparatus. The vacuum chamber was equipped with a zinc-tin alloy cathode (52% Zn). A layer of ZSO5 was deposited on the glass substrate in an oxygen and argon atmosphere by using a method well known to those skilled in the art. The substrate was then transferred to a second vacuum chamber equipped with a cathode made of titanium-zirconium oxide (65 / 35). A layer of TZO65 / 35 was deposited on the first barrier layer in an oxygen and argon atmosphere by using a method well known to those skilled in the art. The obtained sample was heat treated (maintained at 670° C. for 4 minutes). Table 8 shows the optical parameters measured on the coated first substrate according to the second embodiment of the invention. The optical parameters are in external reflection, i.e. in reflection from the glass side of the first monolithic substrate after tempering. The energy transmittance was measured according to standard EN410 (2011) in the wavelength range of 290–2500 nm. TIFF0007637688000008.tif93170

[0068] The above-mentioned examples were then laminated with a second Tedlar substrate by EVA. The solar cell was inserted into the EVA. Certain optical parameters of the laminated assembly were then measured using an Ultrascan spectrophotometer. Table 9 shows the measured values ​​related to external reflectance, i.e., reflectance from the glass side of the first substrate. TIFF0007637688000009.tif96170

[0069] Insertion of solar cells into the laminate of the present invention In an advantageous embodiment, after the EVA was deposited on the first substrate (coated glass corresponding to reference number 5), the solar cell was placed in place, a second EVA film was deposited and finally the second opaque substrate was placed in place. The efficiency of the laminate thus formed and equipped with the solar cell was evaluated under Standard Test Conditions (STC), which required that the cell, kept at 25° C., was irradiated with a power of 1000 watts per square meter with an air mass 1.5 spectrum (standard EN50380, 2003). It was thus shown that when the solar cell received light through the first substrate carrying its layers, the efficiency was reduced by up to 20%, preferably up to 15%, even more preferably up to 10%, with respect to the measurement through the uncoated glass. The efficiency was calculated by measuring the kilowatt-peak (watt-peak) of the cell, which is well known to those skilled in the art and allows the evaluation of the performance of the solar panel in order to predict the amount of electricity it can generate under optimal conditions.

Claims

1. 1. A spandrel panel comprising a first substrate, an intermediate film of polymeric material, and an opaque second substrate, characterized in that the first substrate is covered by up to two layers, including at least an upper dielectric layer, deposited on a surface disposed on the side of the intermediate film of polymeric material.

2. 2. The spandrel panel of claim 1, wherein the upper dielectric layer is characterized by a refractive index at least equal to 2.0 and an absorption coefficient less than 0.

1.

3. 3. The spandrel panel according to claim 1 or 2, characterized in that the upper dielectric layer is an oxide layer, a nitride layer, or an oxynitride layer comprising at least two different elements selected from silicon, titanium, zinc, tin, zirconium, aluminum, and niobium.

4. The spandrel panel according to any one of claims 1 to 3, characterized in that the upper dielectric layer is a mixed titanium-zirconium oxide or a mixed silicon-zirconium nitride.

5. 5. The spandrel panel according to claim 1, wherein the upper dielectric layer has an optical thickness at least equal to 40 nm and at most 110 nm.

6. 6. The spandrel panel of claim 1, wherein an underlayer is deposited on the first substrate between the first substrate and the upper dielectric layer.

7. 7. The spandrel panel of claim 1, wherein the underlayer is an oxide, nitride, or oxynitride layer comprising at least two different elements selected from silicon, titanium, zinc, tin, zirconium, aluminum, and niobium.

8. The spandrel panel according to any one of claims 1 to 7, characterized in that the underlayer is mixed zinc-tin oxide.

9. 9. A spandrel panel according to claim 1, characterized in that the geometric thickness of the lower layer is at least equal to 5 nm and not more than 30 nm.

10. The spandrel panel of any one of claims 1 to 9, wherein the first substrate is characterized by an energy transmittance for light of wavelengths between 300 and 2500 nm that is greater than 0.

68.

11. The spandrel panel according to any one of the preceding claims, characterized by a reflectance measured on the exterior side of 10 to 20%.

12. Parameter a * is −4 to 0, and parameter b * The spandrel panel of any one of claims 1 to 11, characterized by a color in external reflection, wherein:

13. 13. The spandrel panel of claim 1, wherein the second substrate is ordinary glass opacified by a polymeric film or an opaque synthetic substrate.

14. 14. The spandrel panel according to any one of claims 1 to 13, wherein the intermediate film of polymeric material has a thickness of 0.3 to 2 mm and is selected from polyvinyl butyral (PVB), ethylene vinyl acetate (EVA), polyvinyl chloride (PVC), polyurethane (PU), or ionomer.

15. 15. The spandrel panel of claim 1, wherein a solar cell is interposed between the first substrate and the second substrate.

16. 16. The spandrel panel of claim 15, wherein the solar power generation efficiency is reduced by up to 20% versus clear glass under standard test conditions (STC).

Citation Information

Patent Citations

  • Spandrel panel

    EP2517877A2

  • Gold-tinted glazing panels

    GB2311791A

  • Solar power window assembly with solar control characteristics

    JP2013532368A

  • Spandrel coating and method

    US20130022821A1

  • Coloured laminated glass

    US20200009836A1